Respiratory outcomes in preterm neonates (<32 weeks): impact of complete, partial, and absent antenatal steroid exposure - Paul, Bilal A.; Masood, Ashfaq; Ahmed, Syed B.; Bhat, Mushtaq A.; Tramboo, Zubair M.; Bhat, Javeed I. (International Journal of Contemporary Pediatrics, 2025)
Background: Preterm birth is a leading cause of neonatal morbidity and mortality, with respiratory distress syndrome (RDS), bronchopulmonary dysplasia (BPD), and prolonged respiratory support as major complications. While antenatal corticosteroids improve respiratory outcomes, the effects of complete, partial, and absent exposure in infants <32 weeks are inconsistently reported. Aim of the study was to compare respiratory outcomes among preterm neonates <32 weeks based on complete, partial, or no antenatal corticosteroid exposure. Methods: A prospective observational study conducted in the neonatal intensive care unit (NICU) of Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar, from January 2021 to June 2025. 185 preterm neonates <32 weeks gestation were included: complete antenatal corticosteroids (ACS) (n=127), partial ACS (n=41), and no ACS (n=17). Outcomes included incidence and severity of RDS, need for surfactant therapy, need for respiratory support, BPD at 36 weeks postmenstrual age, and mortality. Statistical analysis included Chi-square, Kruskal–Wallis, and multivariate logistic regression. Results: Complete ACS significantly reduced RDS (32.3% versus 46.3% and 58.8%), severe RDS, invasive ventilation, and surfactant use (all p<0.05). Median ventilation duration (3 versus 5 versus 7 days) and time to room air (20 versus 30 versus 50 days) were shortest with complete ACS (p<0.001). BPD (16.5% versus 22.0% versus 58.8%, p<0.001) and mortality (17.3% versus 31.7% versus 52.9%, p=0.002) were also lowest. ACS coverage, gestational age, and birth weight independently predicted outcomes. Conclusions: Complete ACS markedly improves outcomes in preterm infants <32 weeks, underscoring the need for timely administration in high-risk pregnancies.